A Review of Usability Methods and Metrics in Mobile Sport Application - Fitria, Rahma; Faizal Zainul, Mohd; ., Hanif; Hussain, Azham (International Journal of Engineering and Technology, 2018)
Sport activities are very important for personal health. It is claimed that regularly doing physical activity can increase the growth of personal health in term of intellect and psyche, psychological, and confidence. The growth of mobile phone technology can support and motivate people in doing exercise. The statistic shows people spent 52% of all time on digital media on mobile device. There are several factors affecting the usage of mobile application. One of them is the usable design. A technique name usability testing is designed to evaluate product in the user’s perspectives. It is conducted to improve the usability of existing application or to ensure the application being developed is usable. This paper aims to summarise the usability method and metric used to evaluate mobile sport application. Previous related studies are collected from Google Scholar, IEEE Xplore, ACM Digital Library, and Wiley Online Library to create this systematic review. Out of 512 previous studies, 43 are selected based on the criteria. The result shows experimental, questionnaires, and user experience test are the highest usability methods used for mobile sport application. Among these three methods, user experience test is the most method applied. In term of the usability metrics, effectiveness, efficiency, and satisfaction are the most metrics being measured in mobile sport application.